2014
DOI: 10.1021/ac403866g
|View full text |Cite
|
Sign up to set email alerts
|

Detection of miRNA Using a Double-Strand Displacement Biosensor with a Self-Complementary Fluorescent Reporter

Abstract: Design of rapid, selective, and sensitive DNA and ribonucleic acid (RNA) biosensors capable of minimizing false positives from nuclease degradation is crucial for translational research and clinical diagnostics. We present proof-of-principle studies of an innovative micro-ribonucleic acid (miRNA) reporter-probe biosensor that displaces a self-complementary reporter, while target miRNA binds to the probe. The freed reporter folds into a hairpin structure to induce a decrease in the fluorescent signal. The self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 55 publications
(75 reference statements)
2
64
0
Order By: Relevance
“…The intensity decrease continued up to 60 min and no meaningful intensity change occurred afterward. This observation is analogous with those reported in previous publications [12,19] in which a double-strand was also pre-immobilized on a substrate surface before measurements; while, the displacement was completed approximately in 10 min when a double-strand was in a solution without immobilization on the surface [7,11,28]. The Raman spectrum acquired at 60 min of the displacement from the 200 pM sample (black) is also shown in Fig.…”
Section: Optimization Of Hybridization Location Of Idna and Displacemsupporting
confidence: 89%
See 1 more Smart Citation
“…The intensity decrease continued up to 60 min and no meaningful intensity change occurred afterward. This observation is analogous with those reported in previous publications [12,19] in which a double-strand was also pre-immobilized on a substrate surface before measurements; while, the displacement was completed approximately in 10 min when a double-strand was in a solution without immobilization on the surface [7,11,28]. The Raman spectrum acquired at 60 min of the displacement from the 200 pM sample (black) is also shown in Fig.…”
Section: Optimization Of Hybridization Location Of Idna and Displacemsupporting
confidence: 89%
“…Due to these advantages, several biosensors based on toehold-mediated DNA displacement have been recently reported. Larkey et al [11] demonstrated a miRNA fluorescence sensor utilizing fluorescence quenching that occurs when two different dyes tagged at both ends of a freed reporter DNA became close by forming a hairpin structure (limit of detection (LOD): 10 nM). A quartz crystal microbalance (QCM)-based sensing scheme was also studied [12].…”
Section: Introductionmentioning
confidence: 99%
“…[1] miRNAs are often annotated as single sequences,a lthough many length and nucleotide variants of the same miRNA have been identified. [5] Numerous isothermal miRNA amplification methods have been developedt hat utilise the hybridisation chain reaction, [6] DNAzymes and enzymes. [3] The biologicals ignificance of miRNAs has stimulated the development of techniques in which thermally stable polymerases are used to replicate reverse-transcribedm iRNA by thermalc ycling.…”
Section: Introductionmentioning
confidence: 99%
“…

We report a novel sensing method for fluorescence-labelled microRNAs (miRNAs) spotted on an all-dielectric photonic structure. [11][12][13][14][15] Regardless of the strategies adopted for sample preparation, it is nevertheless beneficial to have sensing transduction means capable of enhancing the measured signal at the detection stage. As a result, the Limit of Detection (LoD) is demonstrated to decrease by a factor of about 50.

…”
mentioning
confidence: 99%
“…5 Detecting miRNAs is one of the new challenges of analytical technologies. [11][12][13][14][15] Regardless of the strategies adopted for sample preparation, it is nevertheless beneficial to have sensing transduction means capable of enhancing the measured signal at the detection stage. In an attempt to increase the specificity of recognition while decreasing the minimum detectable amount of miRNA (Limit of Detection, LoD), several detection approaches have been proposed in the past.…”
mentioning
confidence: 99%